Existential Crisis in Matt Haig’s Novel “The Midnight Library” - Amanda Rindunastiti (Morphosis: Journal of Literature, 2024)
The aim of this study is to explore the existential crisis portrayed in Matt Haig's The Midnight Library and to elucidate the defense mechanisms employed by the main character in navigating decision-making. Utilizing a qualitative methodology, this research presents its analysis through a descriptive essay format. The theoretical frameworks guiding this study are Soren Kierkegaard's (1946) existentialist perspective and Anna Freud's (1937) theory of defense mechanisms. Actions and expressions depicted in the novel are categorized according to existentialist themes and analyzed through a psychoanalytic lens. The findings of this study reveal that the existential crises within the narrative encompass themes such as existence preceding essence, freedom, anxiety, alienation, and nothingness, which in turn evoke various defense mechanisms including repression, projection, denial, reaction formation, and rationalization. These defense mechanisms significantly influence the development of the main character's decision-making processes. Keywords: psychoanalysis, existentialism, existential crisis, defense mechanism.